2014
DOI: 10.1177/0886260514526060
|View full text |Cite
|
Sign up to set email alerts
|

Is Length of Shelter Stay and Receipt of a Protection Order Associated With Less Violence and Better Functioning for Abused Women? Outcome Data 4 Months After Receiving Services

Abstract: To provide differential effectiveness on length of stay at a shelter and receipt versus non-receipt of a protection order (PO), and outcomes of violence, functioning, and resiliency, in 300 abused women (150 first-time users of a shelter and 150 first-time applicants for a PO) who participate in a 7-year study with outcomes measured every 4 months. Four months after a shelter stay or application for a PO, abused women staying 21 days or less at a shelter reported similar outcomes compared with women staying lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…All the women in the study were eventually ‘successful’ help‐seekers in terms of accessing specialist DVA services and we can learn from their trajectories. Women's narratives of help‐seeking need to be heard by policy makers and health‐care funders, to inform interventions that facilitate earlier access to services, as highlighted in a recent longitudinal study from the USA reporting a ‘drastic improvement in functioning and resilience and decrease in abuse for all women’ who connected with DVA services . Our study shows that only after connecting with a DVA agency did many women feel that disclosure of abuse and help‐seeking via other formal or informal avenues was legitimized.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…All the women in the study were eventually ‘successful’ help‐seekers in terms of accessing specialist DVA services and we can learn from their trajectories. Women's narratives of help‐seeking need to be heard by policy makers and health‐care funders, to inform interventions that facilitate earlier access to services, as highlighted in a recent longitudinal study from the USA reporting a ‘drastic improvement in functioning and resilience and decrease in abuse for all women’ who connected with DVA services . Our study shows that only after connecting with a DVA agency did many women feel that disclosure of abuse and help‐seeking via other formal or informal avenues was legitimized.…”
Section: Discussionmentioning
confidence: 71%
“…Informal and formal support for women experiencing domestic violence and abuse (DVA) can play a vital role in improving safety, physical and mental health outcomes . Over three quarters of women experiencing DVA disclose the abuse at some point, but disclosure may be limited and come after a long period using private strategies, such as placating or reframing their experiences, to cope within the abusive relationship . Women experiencing abuse tend to have small networks with weak interconnections, partly as a result of coercion from the abusive partner, giving limited opportunities for disclosure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nationally and worldwide, 30% or more of women are likely to have experienced intimate partner violence (IPV). 2 , 3 While many of those women will not experience chronic PTSD symptoms, 4 , 5 a substantial number will. Johnson and Zlotnick, 4 in a prospective study, found that 46.8% of 147 residents of a shelter had PTSD symptoms 6 months after seeking assistance, associated with more severe baseline PTSD symptoms and fewer personal and social resources.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, decreases in abuse and risk for murder are especially important variables for professionals working in this field. Previous analysis revealed that women are at a significantly decreased risk for incidents of violence 4 months after applying for a protection order or after staying at a shelter for abused women (McFarlane, Symes, Maddoux, Gilroy, & Koci, ). All women in this study have reached out for assistance to these two aforementioned ways as a prerequisite for joining the study, so we would expect to see a decrease in violence and risk for murder at 24 months post seeking help as well.…”
Section: Discussionmentioning
confidence: 99%